2005
DOI: 10.1152/japplphysiol.00977.2004
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic modulation of XII motoneuron inspiratory activity does not involve α2-receptor inhibition of theIhcurrent or presynaptic glutamate release

Abstract: . Noradrenergic modulation of XII motoneuron inspiratory activity does not involve ␣ 2-receptor inhibition of the Ih current or presynaptic glutamate release. J Appl Physiol 98: 1297 -1308 ,2005 .FirstpublishedDecember3,2004doi:10.1152/japplphysiol. 00977.2004.-Norepinephrine has powerful and diverse modulatory effects on hypoglossal (XII) motoneuron activity, which is important in maintaining airway patency. The objective was to test two hypotheses that ␣ 2-adrenoceptor-mediated, presynaptic inhibition of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Additionally, ␣ 2 receptors may be on motoneurons themselves, because we found that their direct activation with clonidine hyperpolarizes the motoneurons. Indeed, previous studies have shown that ␣ 2 receptors on motoneurons induce a hyperpolarization by blocking I h currents (Adachi et al 2005;Parkis and Berger 1997;Rekling et al 2000), and such I h currents contribute ϩ10 mV to the resting potential in our chronic spinal rats ). Furthermore, ␣ 2 receptor expression can be detected throughout the spinal cord with the highest densities in the superficial dorsal horn and moderate densities in the portion of be ventral horn containing motoneurons (Giroux et al 1999;Roudet et al 1994).…”
Section: ␣ 2 Receptors Inhibit Epsps But Not Picsmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, ␣ 2 receptors may be on motoneurons themselves, because we found that their direct activation with clonidine hyperpolarizes the motoneurons. Indeed, previous studies have shown that ␣ 2 receptors on motoneurons induce a hyperpolarization by blocking I h currents (Adachi et al 2005;Parkis and Berger 1997;Rekling et al 2000), and such I h currents contribute ϩ10 mV to the resting potential in our chronic spinal rats ). Furthermore, ␣ 2 receptor expression can be detected throughout the spinal cord with the highest densities in the superficial dorsal horn and moderate densities in the portion of be ventral horn containing motoneurons (Giroux et al 1999;Roudet et al 1994).…”
Section: ␣ 2 Receptors Inhibit Epsps But Not Picsmentioning
confidence: 64%
“…NA and other monoamines increase motoneuron excitability (Adachi et al 2005;Elliott and Wallis 1992;Funk et al 1994;Li et al 2004b;Rekling et al 2000) by facilitating persistent inward currents (PICs), consisting of low-voltage activated calcium (Ca PIC) and sodium (Na PIC) currents (Harvey et al 2006b,c;Lee and Heckman 1999). These monoamine-dependent PICs are essential for motoneuron function, amplifying synaptic inputs to motoneurons and providing the basic capacity for sustained depolarization and firing (Harvey et al 2006b;Hounsgaard et al 1988;Lee and Heckman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…5-HT may enhance activity of XII motoneurons by its presynaptic inhibitory action on transmission of glycinergic inhibition (53), and it may reduce XII motoneuronal activity by its presynaptic inhibitory action on transmission of glutamatergic inputs (54), with both mediated by 5-HT 1B receptors. Inhibitory effects mediated by a 2 -adrenoceptors have also been described, but their underlying mechanisms need further studies (55,56). Thus, although we emphasize the postsynaptic excitatory effects because they are best documented in vivo and appear to be most powerful, the net functional effects of the anatomical changes described in our study may be more complex.…”
Section: Functional Implicationsmentioning
confidence: 79%
“…Of note, previous studies have shown that HMs may be subject to an α 2C -adrenoceptor (but not α 2A -adrenoceptor) subtype-mediated inhibition (47,48). However, subsequent studies revealed that this effect is prominent only in neonatal animals (49) and does not involve pre-or postsynaptic inhibition of glutamatergic transmission (50). Thus, the mechanism of action of yohimbine therapy in adult animals probably does not involve the modulation of glutamate transmission of inspiratory drive to HMs through blockade of pre-or postsynaptic α 2C -adrenoceptor subtype.…”
Section: Discussionmentioning
confidence: 97%